2011
DOI: 10.1590/s1517-83822011000100014
|View full text |Cite
|
Sign up to set email alerts
|

The nematicidal effect of some bacterial biofertilizers on Meloidogyne incognita in sandy soil

Abstract: In a greenhouse experiment, the nematicidal effect of some bacterial biofertilizers including the nitrogen fixing bacteria (NFB) Paenibacillus polymyxa (four strains), the phosphate solubilizing bacteria (PSB) Bacillus megaterium (three strains) and the potassium solubilizing bacteria (KSB) B. circulans (three strains) were evaluated individually on tomato plants infested with the root-knot nematode Meloidogyne incognita in potted sandy soil. Comparing with the uninoculated nematode-infested control, the inocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…These products significantly decreased the invasion of J 2 s in the rhizosphere and in the nematode's reproduction in roots (P≤0.05). Also, El-Hadad et al (2011) found positive results regarding the suppression capability of several biofertilizers containing phosphate-solubilizing bacteria, nitrogen-fixing bacteria, and potassium-solubilizing bacteria on rhizosphere-infested M. incognita in greenhouse conditions. To support such finding, the pot experiment conducted in the current study indicated that reproduction of the nematode significantly reduced, in terms of egg masses and RF (P≤0.05), when soil was amended using phosphate, biofertilizer, potassium, Cluster analysis has been carried out using complete linkage method and Euclidean similarity matrix.…”
Section: Discussionmentioning
confidence: 92%
“…These products significantly decreased the invasion of J 2 s in the rhizosphere and in the nematode's reproduction in roots (P≤0.05). Also, El-Hadad et al (2011) found positive results regarding the suppression capability of several biofertilizers containing phosphate-solubilizing bacteria, nitrogen-fixing bacteria, and potassium-solubilizing bacteria on rhizosphere-infested M. incognita in greenhouse conditions. To support such finding, the pot experiment conducted in the current study indicated that reproduction of the nematode significantly reduced, in terms of egg masses and RF (P≤0.05), when soil was amended using phosphate, biofertilizer, potassium, Cluster analysis has been carried out using complete linkage method and Euclidean similarity matrix.…”
Section: Discussionmentioning
confidence: 92%
“…Padgham and Sikora (2007) stated that B. megatherium reduced nematode population by 40%. El-Haddad et al (2011) stated that some beneficial bacteria including the nitrogen fixing bacteria, the phosphate solubilizing bacteria and the potassium solubilizing bacteria significantly reduced the nematode multiplication particularly 60 days after inoculation. These results are in a line with those reported by Zavaleta- Mejia and Van Gundy (1989), who reported that Serratia marcescens suppressed root-knot larvae of Meloidogyne incognita possibly due to the volatile substances produced during its metabolic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Increased phosphorus concentration may lead to reduction in root-knot nematodes. B. megaterium has been evaluated for their effects on a variety of root-knot nematodes [16,17,19,20] reported that B. megaterium greatly reduced numbers of galls, females and egg masses of M. incognita in the roots of sugar-beet followed by B.subtilis, Paecilomyces lilacinus, P. fumosoreus and Trichoderma album respectively. Furthermore, B. megaterium can extensively colonize the rhizosphere and reduce the sugar-beet cyst nematode infection under greenhouse trials [21].…”
Section: Discussionmentioning
confidence: 99%